Ultrasound Stimulation of Prefrontal Cortex Improves Lipopolysaccharide-Induced Depressive-Like Behaviors in Mice - Yi, Sha-sha; Zou, Jun-jie; Meng, Long; Chen, Hou-minji; Hong, Zhong-qiu; Liu, Xiu-fang; Farooq, Umar; Chen, Mo-xian; Lin, Zheng-rong; Zhou, Wei; Ao, Li-juan; Hu, Xi-quan; et al. (Frontiers in Psychiatry, 2022)
Increasing evidence indicates that inflammatory responses may influence brain neurochemical pathways, inducing depressive-like behaviors. Ultrasound deep brain stimulation (UDBS) is a promising non-invasive treatment for neuropsychiatric diseases. We investigated whether UDBS can suppress inflammation and improve depressive-like behavior. Mice were intraperitoneally injected with lipopolysaccharide to induce depressive-like behaviors. Ultrasound wave was delivered into the prefrontal cortex (PFC) for 30 min. Depressive- and anxiety-like behaviors were evaluated through the forced swimming test (FST), tail suspension test (TST), and elevated plus maze (EPM). Biochemical analyses were performed to assess the expression of inflammatory cytokines in the PFC and serum. The results indicated that ultrasound stimulation of the PFC significantly improved depressive-like behaviors in the TST (p < 0.05) and FST (p < 0.05). Anxiety-like behaviors also improved in the EPM (p < 0.05). Furthermore, the lipopolysaccharide-mediated upregulation of IL-6, IL-1β, and TNF-α in the PFC was significantly reduced (p < 0.05) by ultrasound stimulation. In addition, no tissue damage was observed. Overall, UDBS of PFC can effectively improve lipopolysaccharide-induced depressive-like behaviors, possibly through the downregulation of inflammatory cytokines in the PFC. UDBS may be a safe and promising tool for improvement of depression.